ANALISIS PROBLEMATIKA PENERAPAN KURIKULUM MERDEKA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMAN 12 BANDUNG - Cahya Mulyana; Andrea Frendi Zega Ramdani; Nur'ainiyah (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2023)
The development of the era is so rapid, making technology has become part of people's lives. The world of education is no exception, which is increasingly demanded to be able to adapt to the times. Education in the era of society 5.0, which is very closely related to 21st century skills, inspired the Indonesian government to present a new breakthrough curriculum, namely the independent learning curriculum. This also has an effect on concepts and learning systems that are more advanced and flexible, thus demanding all elements of the school to continue to develop and adapt, especially to Islamic Religious Education subjects. The purpose of writing this article is to describe and analyze the problems of implementing the independent curriculum in the subject of Islamic Religious Education at SMAN 12 Bandung. This approach uses qualitative methods, through a phenomenological approach. The results of this study state that the implementation of the Independent Curriculum in schools still faces various problems, especially in the aspects of teachers, students, and infrastructure. This is evidenced by the effectiveness of the learning concept of the Independent Curriculum which has not been maximized.